Implementation Challenges of the Ghana Rent Policy (Act 220) - A Case Study in the Ashanti Region - Ephraim, Lydia; Keelson, Haneef Kwesi; Effah, Samuel (Advances in Social Sciences Research Journal, 2020)
The study sought to find out the implementation challenges of the Ghana rent policy (Act 220) as the country is deficit, in terms of providing rental accommodation to meet its growing population. Geographically, the study through the usage of both probability and non-probability sampling techniques covered suburbs in the Ashanti Region as the region is one of the two most urbanized regions in Ghana. The study employed the explanatory research design in order to ascertain the current state of rental housing in Ghana and as well as what influences rent charges and rental choices. The results from the study indicated that though rental housing is a neglected feature, it has the potential of boosting the revenue base of the nation, provided the policy that governs the sector is well implemented to make the sector organized and provide its socio-economic benefits. The study concluded that the major challenge confronting rental housing in Ghana is the neglect of the sector by the government – ensuring the implementation of the rent policy. This neglect has affected the effective and efficient functioning of the sector which has the potential of helping to address the housing need of the nation while providing income to the individual and the nation.